X射线衍射法残余应力检测的误差影响因素分析 - 王贺权; 张艳聪; 刘元元 (Jixie qiangdu)
The errors of DST-17 stress meter were analyzed by using compared with standard sample.The experimental results indicated that the number of angles has little influence on the fluctuation of measurement errors,but the measurement errors decrease slightly and finally tend to be stable with the increase of the number of angles.However,the diameter of collimating tube has obvious influence on measurement error of residual stress.The measurement error and error fluctuation of 1 mm diameter collimating tube are large.The measurement error of 2 mm diameter collimating tube is basically the same as that of 3 mm diameter collimating tube.The measurement error of SDD detector is smaller than that of linear array detector.The type of detector has little effect on the error fluctuation.